The Relationship Between Level Of Knowledge With Willingness Of Pregnant Women To Doing Covid-19 Vaccination In Godong I Puskesmas - Wiwin Indriati; Wahyu Dewi Hapsari; Dewi Sapta Wati (LPPM AN NUUR, 2023)
Introduction: Covid-19 had attack for everyone, including pregnant women. In Indonesia, data recorded that 536 pregnant women had confirmed Covid-19 during pandemic. More than 50% of these sufferers have not received the Covid-19 vaccination. Lack of knowledge was an obstacle for pregnant women to carry out the Covid-19 program. The purpose of this study was to determine the relationship between the level of knowledge and the willingness of respondents to doing Covid-19 Vacination.Methods: The type of research were quantitative with a correlational design. The approach used is cross sectional. The sample of this study were pregnant women who had not yet had the Covid-19 vaccination with a total sampling was 43 respondents. The data collection is used a questionnaire. Data were analyzed bivariate using Chi Square.Results: The level of knowledge of respondents about Covid-19 Vaccination showed a good level of knowledge, namely 38 (88.4%). In general, 42 (97.7%) respondents stated their willingness to take part in the Covid-19 Vaccination up to the 2nd dose. Bivariate analysis at the level of knowledge and willingness to vaccinate Covid-19 has a significant correlation value of 0.005.Conclusion: There is a relationship between the level of knowledge and the willingness of respondents to vaccinate against Covid-19 with a p-value (0.005)